The Role of Budgetary Control on Managerial Performance in Fertilizer Companies in Indonesia - Hushaini Hasan; Fazli Syam BZ; Mirna Indriani (Universitas Syiah Kuala, 2018)
AbstractObjective – This study aims to examine the influence of budgetary control on managerial performance of fertilizer companies in Indonesia with the characteristics of budgetary goal and knowledge of cost management as moderating variables. Design/methodology – This study uses 144 samples of respondents from middle to upper level managers in the fertilizer industry, i.e. subsidiaries of Pupuk Indonesia. Data collection is carried out by utilizing survey questionnaires. Data analysis is performed using Moderating Regression Analysis (MRA). Results – The findings indicate that budgetary control, characteristics of budgetary goal and knowledge of cost management influence managerial performance. Furthermore, characteristics of budgetary goal and knowledge of cost management was found to moderate the influence of budgetary control on managerial performance. Research limitations/implications – This study is only limited to the companies that are engaged in the fertilizer industry, hence its results cannot be used for the purpose of generalization. Apart from that, the characteristics of budgetary goals and knowledge of cost management variables in this study are only quasi moderator variables.